2023
DOI: 10.1001/jama.2023.4221
|View full text |Cite
|
Sign up to set email alerts
|

Emulation of Randomized Clinical Trials With Nonrandomized Database Analyses

Abstract: ImportanceNonrandomized studies using insurance claims databases can be analyzed to produce real-world evidence on the effectiveness of medical products. Given the lack of baseline randomization and measurement issues, concerns exist about whether such studies produce unbiased treatment effect estimates.ObjectiveTo emulate the design of 30 completed and 2 ongoing randomized clinical trials (RCTs) of medications with database studies using observational analogues of the RCT design parameters (population, interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
85
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 54 publications
2
85
1
Order By: Relevance
“…To the Editor A recent study sought to compare the effect estimates among 32 RCTs and corresponding observational study analogues. Using the target trial framework, the authors found moderate to high correlation between RCT effect estimates and their observational counterparts, with the highest correlation observed when observational emulation methods more closely approximated RCT design.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor A recent study sought to compare the effect estimates among 32 RCTs and corresponding observational study analogues. Using the target trial framework, the authors found moderate to high correlation between RCT effect estimates and their observational counterparts, with the highest correlation observed when observational emulation methods more closely approximated RCT design.…”
mentioning
confidence: 99%
“…In this study, Dr Wang and colleagues used a 1:1 propensity score nearest-neighbor matching approach to achieve observed confounder balance between treatment groups. It is our understanding that this analytic approach yields estimates of the average effect in the overlap population (if a caliper were used to restrict matching to pairs with similar propensity scores and not all patients in the treatment groups were matched) or the average effect in the treated and untreated populations (if no caliper were used and all patients receiving at least 1 treatment dose were matched).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We write in response to the recent article about the emulation of randomized clinical trials (RCTs) with nonrandomized database analyses.…”
mentioning
confidence: 99%
“…The important work of this study evaluating consistency between database analyses and randomized data serves as a reminder that thoughtful conduct of observational data analysis is a necessity and not something that can be overcome simply by the insistence of only accepting inference from randomized studies.…”
mentioning
confidence: 99%